P4_5 Star Wars Han's Solo Journey - Graham, Holly; Howard-Clark, Simon; Sainty, William; Kneeshaw, Sam (Physics Special Topics, 2017)
The Star Wars saga has its fair share of impossible feats being performed on a regular basis throughout the lms. In this paper we calculated how long the infamous Kessel Run would take Han Solo in the Millennium Falcon from his perspective at a velocity of 99% of the speed of light, and the perspective of an observer watching his journey unfold. We calculated his journey would take almost 40 years from the reference frame of an observer but would appear to only take 5.64 years from Han Solo's reference frame. The length contraction of the Falcon is also calculated and an observer in the galaxy would see the Falcon to be a mere 4.9 m long, 14% of its original size.